1972
DOI: 10.1073/pnas.69.12.3570
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-Dependent Inactivation of RNA Polymerase from Bacillus brevis

Abstract: RNA polymerase has been purified from vegetative cells of Bacillus brevis and resolved into 'core' enzyme and sigma factor. The purified enzyme is rapidly inactivated by incubation at low temperatures in the presence of 1-2 mM ATP, dATP, or NAD+, while other nucleotides at this concentration have little or no effect. Inactivation is not accompanied by the incorporation of an adenylyl or phosphoryl moiety into RNA polymerase; nevertheless, it is essentially irreversible. DNA, high concentrations of glycerol, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Partial and similar results were reported by Novello and Stirpe (1969). Sarkar and Paulus (1972) reported an inactivation by ATP of a purified bacterial RNA po~ymerase. However, there a:e several differences between their report and our results.…”
Section: Discussionsupporting
confidence: 78%
“…Partial and similar results were reported by Novello and Stirpe (1969). Sarkar and Paulus (1972) reported an inactivation by ATP of a purified bacterial RNA po~ymerase. However, there a:e several differences between their report and our results.…”
Section: Discussionsupporting
confidence: 78%
“…We also consider important the finding that the antibiotics are found to bind B. brevis Nagano DNA with an efficiency analogous to their ability to inhibit transcription in vitro (gramicidin S > tyrocidine > tyrothricin > linear gramicidin). From the information available these results could argue for a stronger affinity of gramicidin S for B. brevis Nagano template, since it has been reported that 10 pg gramicidin S can inhibit transcription in B. brevis ATCC 8 185 (a non-producer of gramicidin S) only to about 23 %, whereas tyrothricin, tyrocidine, or linear gramicidin (produced by the B. brevis ATCC 8 185 strain) tested at the same concentration caused 96%, 100% and 90% inhibition of transcription respectively (Sarkar & Paulus, 1972a).…”
Section: Discussionmentioning
confidence: 95%
“…3 b), and the molar ratios were calculated from the densitometer tracings. The major components had approximate molecular weights of 150000 f: 10000; 65000 5000, and 38000 +_ 1000, and occurred in molar ratios of about 2.6 : 1-3 : 3 i-0.4, thus corresponding well to the p + p', CT, and a subunits of RNA polymerase from B. brevis ATCC 81 85 (Sarkar & Paulus, 19726) and B. subtilis (Avila et al, 1971). Subunit a was found in higher ratios than subunits fl p' in a number of preparations, and this was attributed to impurities running very close to the a band of the gels (Fig.…”
Section: Composition and Properties Of Rna Polymerasementioning
confidence: 99%
See 2 more Smart Citations